2003
DOI: 10.1039/b307476e
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex-PCR and PCR-RFLP assays to monitor water quality against pathogenic bacteria

Abstract: In this work we developed and optimized two molecular-based approaches to monitor rapidly, sensitively and specifically bacterial pathogens from three different genera, Escherichia coli, Pseudomonas aeruginosa, and Salmonella spp., directly in waters. To achieve this aim, firstly a multiplex-PCR assay (M-PCR) was optimized using a primer pair specific for each pathogen. Secondly, as a molecular confirmatory test after isolation of the pathogens by classical microbiological methods, PCR-RFLP of their amplified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…MPCR methods for detecting several genes of these bacteria have been reported previously for E. coli O157:H7 (9,10,13,16,(21)(22)(23)(24), Salmonella spp (13,21,(25)(26)(27), and V. cholerae (21,28,29 ). However, none of the reported MPCR methods simultaneously detected all three viable pathogens present in the same sample.…”
mentioning
confidence: 99%
“…MPCR methods for detecting several genes of these bacteria have been reported previously for E. coli O157:H7 (9,10,13,16,(21)(22)(23)(24), Salmonella spp (13,21,(25)(26)(27), and V. cholerae (21,28,29 ). However, none of the reported MPCR methods simultaneously detected all three viable pathogens present in the same sample.…”
mentioning
confidence: 99%
“…Culture-based detection can be time consuming and does not account for viable but nonculturable strains (Iijima et al, 2007;Khan et al, 2007;Ram et al, 2008). Molecular methods including PCR are faster, can detect all viable bacteria in a sample, and can also detect pathogens in very low concentrations (Abd-El-Haleem et al, 2003). However, one of the major disadvantages of PCR as it relates to environmental samples is that there is a window of opportunity where it can detect non-viable bacteria (i.e.…”
Section: Microbial Contamination In Private Systemsmentioning
confidence: 99%
“…2). Previously, Abd-El- Haleem et al (2003), reported that HinfI is the most suitable enzyme for RFLP analysis for the 16S rDNA amplicons.…”
Section: Pcr-rflp Fingerprints Of the 16s Rdna Genementioning
confidence: 99%